Ethnobotanical Study of Medicinal Plants in South Sumatera, Indonesia - Asiandu, Angga Puja; Sari, Widya (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2024)
South Sumatra, a province in Indonesia, is inhabited by several tribes. The geographical landscape surrounded by primary and secondary forests is a natural resource for the local communities in dealing with medical problems. They use plants as traditional medicine from generation to generation. The used parts include roots, stems, leaves, and sap that are biologically active to treat some diseases from moderate to deadly diseases. Based on literature studies, there are 250 plant species from 79 families processed by local communities in South Sumatra in some ethnobotanical activities. The dominant plant families are Fabaceae (5.6%), Asteraceae (4.8%), Euphorbiaceae (4.4%), Poaceae (4.4%), Myrtaceae (3.6%), Rubiaceae (3.6%), Rutaceae (3.6%), Solanaceae (3.6%), and Piperaceae (3.2%). Among many methods, boiling is the most common method in processing medicinal plants as it is considered more effective in extracting the bioactive compounds.